Financial globalization in emerging countries: Diversification vs. offshoring - Francisco Ceballos; Tatiana Didier; Sergio L. Schmukler (Asian Development Bank Institute (ADBI), 2012)
Financial globalization has gathered attention since the early 1990s because of its macro-financial and crisis implications and its perceived large expansion. But financial globalization has taken different forms over time. This paper examines two important concurrent dimensions of financial globalization relevant for emerging countries: diversification and offshoring. The diversification dimension of globalization refers to the increase in foreign assets and liabilities in countries' portfolios. Offshoring, instead, is related to the reallocation of financial activities to international markets, namely, to where transactions take place regardless of who holds the assets. We find that globalization via the diversification channel has expanded throughout during the 2000s as domestic residents invested more abroad and foreigners increased their domestic investments. However, financial globalization via offshoring has displayed more mixed patterns, with variations across markets and countries. We also show that the nature of financing through both diversification and offshoring has improved for emerging countries.
Keywords: F36; G15; G204; 330; financial globalization; emerging economies; diversification; offshoring; Finanzmarktregulierung; Kapitalmobilität; Finanzplatz; Standortwettbewerb; Schwellenländer; Welt